Neck strength imbalance correlates with increased head acceleration in soccer heading - Dezman, Z. D. W.; Ledet, E. H.; Kerr, H. A. (Sports Health: A Multidisciplinary Approach, 2013)
Background: Soccer heading is using the head to directly contact the ball, often to advance the ball down the field or score. It is a skill fundamental to the game, yet it has come under scrutiny. Repeated subclinical effects of heading may compound over time, resulting in neurologic deficits. Greater head accelerations are linked to brain injury. Developing an understanding of how the neck muscles help stabilize and reduce head acceleration during impact may help prevent brain injury.